Alkaline earth metal alloys of Cu for enhanced catalytic activity toward CO2 hydrogenation - Thakkar, Kavita; Joshi, Kavita (My University, 2022)
CO2, a well-known greenhouse gas, is a potential raw material used to produce various chemicals. Dissociation of CO2 to CO or hydrogenation to formate (HCOO) or carboxyl (COOH) intermediate is crucial in determining the reaction pathway for CO2 conversion. In this work, we demonstrate that alloys of Mg-Cu exhibit greater activity toward activation and hydrogenation of CO2 than transition metal alloys reported so far. Two different compositions of Mg-Cu, namely Mg2Cu and MgCu2, have been studied using periodic Density Functional Theory (DFT). Our investigations reveal that CO2 chemisorbs on both bimetallic alloys. Coadsorption of CO2 with H2O leads to the spontaneous formation of COOH∗ over Mg2Cu(224), whereas a negligible barrier (0.04 eV) is observed for MgCu2 (311). HCOO∗ formation has a barrier of 0.34 eV and 0.42 eV on Mg2Cu(224) and MgCu2(311), respectively. Dissociation of CO2 to CO is kinetically unfavorable on both compositions of Mg-Cu. We provide a rationale for the observed activity by analyzing the electronic structure. Notably, the spontaneous hydrogenation of CO2 makes earth-abundant metals suitable candidates for alloying that await experimental verification.
Keywords: Earth Metal Alloys; CO2 hydrogeneration